Molecular profile of glioblastoma and its clinical correlations - Correa-Silva, MH; Cirelli-Moraes, A; Maria, DA (Seven Editora, 2023)
Glioblastoma multiforme (GBM) is a malignant neoplasm of the central nervous system that is highly invasive and has a poor prognosis, with an average patient survival of 15 to 17 months. It is characterized by amplification of the epidermal growth factor receptor (EGFR) gene, overexpression of the EGFR protein, and loss of the tumor suppressor gene phosphatase and tensin homolog (PTEN). And the secondary form, which accounts for about 10% of cases, is associated with the younger age of the patient and arises from the progression of low-grade gliomas. It has a better prognosis and usually has mutations in the isocitrate dehydrogenase 1 (IDH1) and tumor protein 53 (TP53) genes. However, detailed knowledge about the heterogeneity of molecular alterations of the tumor may contribute to the prognosis of the patient and his response to treatment and to the improvement of current therapeutic strategies, besides contributing to the development of new strategies and treatment protocols for this type of tumor. DOI: https://doi.org/10.56238/colleinternhealthscienv1-069